Superhydrophobic, Surfactant‐doped, Conducting Polymers for Electrochemically Reversible Adsorption of Organic Contaminants. (22nd June 2018) - Ren, Yinying; Lin, Zhou; Mao, Xianwen; Tian, Wenda; Van Voorhis, Troy; Hatton, T. Alan
Abstract: Polymeric adsorbents show great potential for the replacement of activated carbon for removing a wide range of toxic organic pollutants from wastewater streams since they do not suffer from costly regeneration needs and high attrition rates. Herein, an electrochemically regenerable polymeric adsorbent based on an intrinsically conducting polymer (CP), polypyrrole (PPy), doped with anionic surfactant dioctylsulfosuccinate (AOT), denoted PPy(AOT), for mitigating organic pollutants in wastewater is reported. A facile electropolymerization protocol to synthesize highly porous PPy(AOT) is developed, with an adsorption capacity of greater than 570 mg pollutant/g polymer in its superhydrophobic oxidized state. It is demonstrated that the hydrophobicity of PPy(AOT) and hence its affinity for organics can be modulated electrochemically through the re‐orientation of AOT dopants, which can be exploited to regenerate the adsorbent and use it repeatedly for multiple adsorption/desorption cycles. It also explores the interactions between the adsorbed organic molecules and the surfactant‐doped CP adsorbent using a combined density functional theory and molecular dynamics approach to elucidate the mechanism of electrochemical modulations of hydrophobicity and affinity of the material. The physicochemical insights are significant for developing broader applications of such material in drug delivery, sensing, self‐cleaning surfaces, microfluidics, and artificial muscles. Abstract : Highly porous surfactant‐doped conducting polymer exhibits superhydrophobicity in the oxidized state, and its hydrophobicity and hence affinity for organics can be electrochemically modulated. The switchable hydrophobicity is due to the re‐orientation of dopants with respect to the polymer backbone, which can be exploited to regenerate the adsorbent and use it repeatedly for multiple adsorption/desorption cycles.